A brief history of pollution - Markham, Adam (St. Martinis Press / New York, 1994)
Table of Contents 1. A Brief History of Pollution 2. The City as Source of Pollution 3. Why Care? Pollution, Nature and Ethics 4. The First Consumer Revolution 5. Water Pollution and Chemical Contamination 6. The Poisoned Atmosphere 7. An All Consuming Passion 8. Energy and Survival 9. Pollution in the Making: The Example of Asia 10. The Politics of Pollution